O efeito da press??o do tempo na neglig??ncia da omiss??o de informa????es: um estudo experimental - Prado, Rejane Alexandrina Domingues Pereira do (2015)
The term omission neglect encompasses the insensitivity of the consumer before the lack of information about such aspects as products and/or service characteristics, quality and options, as well as other factors. Omission neglect occurs when only part of the necessary information for analysis is present. Furthermore, this lack of information may not even be noticed, which leads to negligence in the decision-making process. This phenomenon has been studied since 1998, beginning in the United States, and has been researched in different contexts since then. However, studies on the effect of time pressure on omission neglect has not been found so far, which sets up a new investigation problem. Because individuals may not recognize omission of information in the purchase decision processes, notably in the evaluation of alternatives, consumption mistakes of either lower or higher degree may occur. Also, considering that time pressure is a factor that may also damage the quality of decisions, this study tried to identify the time pressure effect on omission neglect. Eight hypotheses were tested in two different experiments. The results allowed us to identify the time pressure effect on the negligence of information omission, the non-congruence between subjective expertise and objective expertise, and also identified that omission salience cancels the time pressure effect.